THE ROLE OF TIME MANAGEMENT IN THE DEVELOPMENT OF MEDIKAL EDUCATION - Дікал, Мар’яна; Копчук, Тамара; Драчук, Віра (SWorldJournal, 2024)
Time management for medical university educators is a key element of successful and effective education. Educators bear a significant workload, including teaching, research activities, interaction with students, administrative tasks, and more. Several tim